Creative Brand Publicity in Outdoor Advertising: An Analysis of Gojek Billboard Using CBP Theory - Vega Ismaryani Putri; Indri Anggraini; Natasya Sarah Mountina (Jobmark: Journal of Branding and Marketing Communication, 2023)
In 2017, Gojek captured public attention through a distinctive billboard campaign at the Kuningan intersection in Jakarta. The billboard featured a minimalist design with long text narrating everyday stories, creating a striking departure from conventional outdoor advertising. This phenomenon reflects the growing importance of creative brand publicity in shaping consumer perceptions. This study analyzes the campaign through the lens of Creative Brand Publicity (CBP) theory, focusing on the integration of Mood, Moment, and Movement as core elements of brand communication. A qualitative descriptive approach was employed, involving textual analysis of billboard content, observation of audience responses, and examination of social media interactions that amplified the campaign’s reach. The findings reveal that Gojek’s billboard successfully elicited emotional resonance, strengthened brand awareness, and reinforced its image as a relatable, human-centered brand. The campaign’s virality on digital platforms demonstrated how offline publicity can seamlessly extend into online engagement, producing significant audience interaction. Notably, the study highlights that billboard effectiveness is not determined solely by location or visual appeal, but by the brand’s ability to deliver relevant narratives that resonate with everyday experiences. Theoretically, this research contributes to the development of CBP theory by demonstrating the contextual application of its three elements in producing wide publicity and meaningful audience engagement. In practice, the insights provide guidance to marketers on designing outdoor advertising strategies that combine simplicity, emotional appeal, and narrative relevance to achieve effective brand communication.